Attenuated isolated 3' signal: A highly challenging therapy relevant ALK FISH pattern in NSCLC. (May 2020) - Smuk, Gábor; Pajor, Gábor; Szuhai, Károly; Morreau, Hans; Kocsmár, Ildikó; Kocsmár, Éva; Pajor, László; Kajtár, Béla; Sárosi, Veronika; Lotz, Gábor; Tornóczky, Tamás
Highlights: We show cases featured with a unique massive reduction of the 3′ ALK FISH signal. This therapy relevant pattern (termed downstream deletion) can be easily overlooked. In-depth imaging, IHC and Anchored Multiplex PCR based NGS confirmed positivity. ALK downstream deletion should be included in official diagnostic guidelines. Enquiry of any unique ALK FISH patterns is important to avoid false diagnosis. Abstract: Objectives: Targeted therapies in the management of patients with lung cancer provide significantly better outcome compared to chemotherapy. Detection of the anaplastic lymphoma kinase (ALK) gene rearrangement has great predictive value for treatment with small molecule tyrosine kinase inhibitor (crizotinib and alectinib commonly). Fluorescent in situ hybridisation (FISH) assay is a basic diagnostic test designed for detecting ALK gene rearrangements. Although being considered as gold standard method by IASLC's guideline, it is often regarded as difficult and error prone. Our aim was to examine a unique atypical ALK FISH pattern, revealed during a systematic large-scale monitoring, which carries the great risk of misinterpretation, hence may result in loss of patients eligible for targeted therapy. Materials and Methods: Tissue and cytology samples from nearly one thousand patients with advanced stage non-small cell lung cancer (NSCLC, n = 996) were routinely examined by ALK FISH and immunohistochemistry (Ventana ALK-D5F3-CDx assay). Anchored Multiplex PCR based Next Generation Sequencing (AMP-NGS) was used to detect fusion gene transcripts in ambiguous cases. Results: Fifty-nine (5, 9%) of the cases were positive with ALK FISH test. Three cases showed atypical pattern with a significantly reduced sized red (3′) signal and complete loss of green signals. Digital signal measurement confirmed this finding, showing consistent attenuation of 3′ signals throughout the tumours. In all three cases AMP-NGS and ALK IHC verified the presence of a fusion gene and expressed oncoprotein, respectively. Conclusion: Approximately 5% of the 59 ALK positive cases exhibited atypical attenuated isolated 3′ signal pattern. The immunohistochemistry and AMP-NGS examinations helped to clarify the presence of oncoprotein and the fusion gene, respectively. Our results emphasize the importance of extensive exploration of the genetic background of any unexpected FISH finding to avoid false diagnosis. This enables clinicians to indicate the adequate therapy with higher efficiency for patients suffering from NSCLC.